2011
DOI: 10.1002/app.34490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boric acid treatment method on the characteristics of poly(vinyl alcohol)/iodine polarizing film

Abstract: Four types of polyvinyl alcohol (PVA)/iodine complex films were made using different boric acid treatments to prepare polarizing films having high durability under humid and warm atmospheres and to identify the effects of the boric acid treatment method on the formation of the PVA/iodine polarizing film. The four types of films were a PVA iodinated film(I), a PVA film that was iodinated and then treated with boric acid(I-B), a PVA film that was treated with boric acid and then iodinated(B-I), and a PVA film th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…High amounts of solvents such as acetone, DMF, methanol, ethanol, pyridine, or formic acid, will destroy the complex and the color will fade. Shin et al [173,174] reported the use of boric acid treatment to form I 2 PVA polarizing film characterized by its transmittance and polarization degree. The acid promoted the formation of iodide species I 3¯ and I 5¯, and improved the durability of the film under heat and humidity.…”
Section: Iodine-proteinic Fiber Complexesmentioning
confidence: 99%
“…High amounts of solvents such as acetone, DMF, methanol, ethanol, pyridine, or formic acid, will destroy the complex and the color will fade. Shin et al [173,174] reported the use of boric acid treatment to form I 2 PVA polarizing film characterized by its transmittance and polarization degree. The acid promoted the formation of iodide species I 3¯ and I 5¯, and improved the durability of the film under heat and humidity.…”
Section: Iodine-proteinic Fiber Complexesmentioning
confidence: 99%
“…Figure a–c shows and compares the UV–visible absorption spectra of PVA‐SbQ films (P‐I) and PVA‐SbQ films (P‐I‐B) of a) MQ2011, b) MQ2012 and c) MQ2013. In these spectra, absorption bands at 200, 290, 360, 470 and 600 nm are identified as being derived from I − , I 3 − , free I 2 I 3 − , PVA–I 3 − and PVA–I 5 − complex . We can see the presence of I − , I 3 − and free I 2 I 3 − in the films (P‐I) in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The complexes and structures of polyiodines with poly(vinyl alcohol) (PVA) and other polymers have been studied and discussed for many years, and have been applied to polarizer films for actual use, such as being used as an important component of liquid crystal displays. Aggregation models for PVA–I 3 − and PVA–I 5 − complexes have been suggested, which are enveloped by four PVA segments of syndiotactic configuration with extended conformation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the maximum demand for polarizers is in the area of liquid crystal displays (LCDs). PVA-iodine polarizing films, which exhibit the highest polarization efficiency among commercial polarizers, are mainly used in this area [1][2][3]. However, PVA-based polarizing films should be protected by tri-acetyl cellulose (TAC) because of their low stability.…”
Section: Introductionmentioning
confidence: 99%